Grazoprevir plus peginterferon and ribavirin in treatment‐naive patients with hepatitis C virus genotype 1 infection: a randomized trial. Issue 2 (10th September 2015) - Lagging, M.; Brown, A.; Mantry, P. S.; Ramji, A.; Weilert, F.; Vierling, J. M.; Howe, A.; Gendrano, I. N.; Hwang, P.; Zhang, B.; Wahl, J.; Robertson, M.; et al.
Summary: Grazoprevir (MK‐5172, Merck & Co., Inc.) is a selective inhibitor of the hepatitis C virus (HCV) NS3/4a protease. The aim of this study was to evaluate the safety and efficacy of grazoprevir at doses of 25–100 mg/day in combination with peginterferon and ribavirin (PEG‐IFN/RBV). In this randomized, dose‐ranging, multicentre trial, treatment‐naive adults with chronic HCV genotype 1 infection received once‐daily grazoprevir 25 mg, 50 mg or 100 mg plus PEG‐IFN/RBV for 12 weeks. Patients with quantifiable HCV RNA (≥25 IU/mL) at week 4 received an additional 12 weeks of PEG‐IFN/RBV. The primary endpoint was sustained virologic response (HCV RNA <25 IU/mL 12 weeks after completing therapy [SVR12]). Eighty‐seven patients were randomly assigned and received ≥1 dose of therapy. Median time to undetectable HCV RNA was 16 days in the 100‐mg arm and 22 days in the 25‐ and 50‐mg arms. All patients except one had HCV RNA undetectable or unquantifiable at week 4 and received 12 weeks of therapy. SVR12 was achieved by 13 of 24 (54.2%), 21 of 25 (84.0%) and 23 of 26 (88.5%) patients in the 25‐, 50‐ and 100‐mg arms, respectively (per‐protocol analysis). Three patients discontinued as a result of nonserious adverse events (AEs) and three patients experienced serious AEs. Transaminase elevations occurred in two patients (one each in the 25‐ and 100‐mg arms). Conclusion: These data support further study of the grazoprevir 100‐mg dose. Phase 3 studies of grazoprevir 100 mg in combination with elbasvir are currently ongoing (NCT01710501; protocol P038).